العوامل المؤثرة على استقلالية المراجع الخارجي الليبي - أنس عبد القادر عامر, (Scientific Journal of University of Benghazi, 2020)
This is an analytical study aimed to identify the Factors Influence on Libyan External Auditor Independence. The study objective is to determine the most important factors Influence on Libyan External Auditor Independence which was as follow. Audit fees, Non audit fees, Auditor office size, Client size, Audit Tenure, Audit profession Regulations, competition of audit market, and Audit committees. The results showed that a positive relationship between audit fees, Non audit fees, Audit profession Regulations, competition of audit market, and Audit committees, In addition, there is a Negative relationship between Auditor office size, Client size, Audit Tenure.